Association between dietary index for gut microbiota and self-reported severe headache or migraine in U.S. adults: a cross-sectional study from NHANES - Liu, Jingjing; Liu, Hailian; Li, Weiyi; Huang, Shaoqiang (Frontiers in Nutrition, 2025)
BackgroundThe diet–microbiota–gut–brain axis is an emerging frontier in brain health, with microbiota-targeted dietary interventions offering potential benefits. This study aimed to explore the association between the recently introduced dietary index for gut microbiota (DI-GM) and self-reported severe headache or migraine in U.S. adults.MethodsThis cross-sectional study analyzed the National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2004. Severe headache or migraine was determined based on participants’ responses to the question: “Have you had a severe headache or migraine in the past 3 months?” The DI-GM was calculated from dietary recall data. Multivariable logistic regression models were performed to evaluate the odds ratio (OR) and 95% confidence interval (95% CI) for the association between DI-GM and severe headache or migraine. Secondary analyses included restricted cubic splines (RCS) and subgroup analyses.ResultsAfter adjustments, a higher DI-GM score and BGMS were associated with a lower prevalence of severe headache or migraine (DI-GM: OR = 0.95, 95% CI = 0.91–0.99, p = 0.011; BGMS: OR = 0.90, 95% CI = 0.85–0.96, p = 0.003). RCS showed a linear relationship between DI-GM and severe headache or migraine. In two-piecewise regression models, the adjusted OR for developing a severe headache or migraine was 0.90 (95% CI = 0.85–0.97, p = 0.005) in participants with a DI-GM score ≥ 4, whereas no association was observed in those with a DI-GM score < 4.ConclusionThe DI-GM was negatively associated with the prevalence of self-reported severe headache or migraine in U.S. adults, particularly when scores exceeded 4.